Post-heroic leadership, tempered radicalism and senior leaders as change agents for gender equality - Kelan, Elisabeth K.; Wratil, P. (Elsevier, 2017)
Micro change agents for gender equality in organisations are often considered to be tempered radicals who work within an existing structure for changing the status quo. However for gender equality to happen, it is often claimed that heroic leadership of top leaders, or macro change agents, is required. The aim of this article is to show how CEOs as macro change agents for gender equality can be conceptualised. Drawing on interviews with 20 global CEOs and a literature review, the article develops a framework to conceptualise how CEOs are fostering gender equality around accountability, building ownership, communicating, leading by example, initiating and driving culture change. The article questions the conceptualisation of change agents of gender equality as either tempered radicals, for micro change agents, or heroic leaders, for macro change agents, and argues instead that to be macro change agents for gender equality, CEOs need to display post-heroic leadership and tempered radicalism to foster change in regard to gender relations
Keywords: Chief Executive Officers; Leadership; Macro Change Agents; gender; Top Management